Export-platform foreign direct investment: The Irish experience - Frank Barry (EIB Papers, 2004)
Ireland is the most successful EU economy in attracting export-platform foreign direct investment (FDI), and the increased FDI inflows of the 1990s are widely agreed to have been one of the most important factors in generating the remarkable boom that the country experienced over that decade. The present paper considers the confluence of factors - domestic policy changes, fortuitous developments in the European and global economic environment, and the coming to fruition of policy initiatives of earlier eras - that provided the setting for the increased inflows of the period and the changes that they wrought. One of the main findings is that growth-enhancing economic policies - including fiscal prudence, the maintenance of labour-market flexibility and a focus on scienceoriented human capital formation - were crucial for Ireland to derive the full benefits of its FDI-attracting low-corporation-tax regime.
Keywords: 330; Direktinvestition; Investitionspolitik; Wirtschaftspolitik; Wirtschaftswachstum; Irland